A Review on the Selection of Granular Fertiliser Distribution Methods for Malaysia's Paddy Field on a Large Scale (Journal of Business Management and Accounting, 2016)
High efficiency distribution applicators, such as boom sprayer (air blower concept), Kuhn Axis fertiliser spreaders (rotating disc concept), and pendulum spreader (magnetic concept) were the response to the call to distribute granular fertiliser to a paddy field on a large scale. Each of these distribution applicators had their own characteristics which are optimised for different purposes. This paper shows the review results after studying journal papers to select the most suitable applicators for Malaysia’s paddy field on a large scale. The analyses included the compliments of these applicators toward the type of granular fertiliser used in Malaysia’s paddy field, the maintenance cost  of  these  applicators,  the  suitability  of  machine  to  be  used  in  the  landscape  of Malaysia’s paddy, the distribution areas covered by these applicators, and the accuracy of distribution. The review concluded that Kuhn Axis fertiliser spreader was found to be the most suitable applicator compared to other applicators.